Pengaruh Pemberian Ekstrak Kering Daun Pepaya Dengan Pelarut Air Terhadap Waktu Penyembuhan Luka Bakar Derajat II Dangkal Pada Tikus Putih - Styawan, Agus Prawita (Coping: Community of Publishing in Nursing; Vol 2 No 1 (2014): JURNAL EDISI JANUARI-APRIL 2014, 2014)
The most often occurs of burn cases are second degree (76.9%). The purpose of the treatment are, preventing infection and allowing the remains to proliferating epithelial cells and close the wound surface. Papaya leaf extract can be used as an antiseptic and healing burns had inhibitory effects against bacteria and stimulate the formation of collagen. The purpose of this research is to determine the effect of extract of dried papaya (Carica papaya) with solvent water for healing time second degree superficial burns in rats (Rattus novergicus). Design of this study is true experiment with posttest-only design with control group design. The research was conducted at the Laboratory Animal Unit of Pharmacology Faculty of Medicine, Udayana on May 16, 2013 to June 8, 2013. The treatment group consisted of dried extract treatment by administering an aqueous solution consisting of 5 treatments that solution concentration 0%, 25%, 50%, 75% and 100% with five repetitions. The analysis used parametric test Anova and Post hoc test. Results showed no difference in the healing time of superficial II degree burns significant between concentration (p=0,438). The conclusion of this research is the fastest healing process is 16.2 days with concentration 75% and the slowest healing process is 20,2 days with  concentration 100% however there was not significant differences effect of extract papaya with other concentration.
Keywords: Dry Leaf Extract Papaya, Water Solvents, Burn Wound Healing Time